Human Tissue Factor Pathway Inhibitor Fused to CD4 Binds both FXa and TF/FVIIa at the Cell Surface - Riesbeck, Kristian; Dorling, Anthony; Kemball-Cook, Geoffrey; McVey, John H; Jones, Mick; Tuddenham, Edward G D; Lechler, Robert I (Thrombosis and Haemostasis, 1997)
Tissue factor pathway inhibitor (TFPI) is one of the main regulators of the tissue factor (TF) pathway of coagulation. To tether human TFPI to the cell surface, full length or truncated TFPI lacking the third Kunitz domain were fused with domains three and four and the carboxy-termi- nal sequence of human CD4. Constructs were transfected into a mouse fibroblast cell line and individual clones were checked for expression using monoclonal antibodies directed against the first two TFPI Kunitz domains and against CD4. Specific human FXa binding was detected by flow cytometry using an anti-FX polyclonal antibody, and inhibition of FXa proteolytic activity was verified by chromogenic substrate assay using S-2765. In addition, TFPI-CD4-expressing cells, preincubated with FXa, specifically bound human TF-FVIIa complexes as revealed with an anti-human TF polyclonal antibody. No functional difference was observed between full length or truncated TFPI-CD4. These results demonstrate that functionally intact TFPI can be tethered to the cell surface. Genetic manipulation of, for example, endothelial cells leading to the stable expression of TFPI may inhibit the development of coronary artery heart disease following cardiac allotransplantation, and may inhibit thrombosis in the context of xenotransplantation.